Solution processing grown Alq3 microwires for volatile organic compound vapor sensing - DUMLUDAĞ, FATİH (American Scientific Publishers, 2014)
The sensitivities of Alq3 micowires based chemiresistor to different volatile organic compound (VOC) vapors were examined. Sensor responses were measured as changes in current at constant voltage. Adsorption models, based on the assumption of the pseudo first-order, pseudo second order mechanism, Ritchie and Elovich equation were applied to examine the kinetics of the VOC vapor adsorption. The rate constants, equilibrium capacities and related correlation coefficients for each kinetic model were calculated and discussed. The results showed that kinetic data were followed fitting the pseudo second-order model than the pseudo first-order, Ritchie and Elovich equation. Copyright © 2014 American Scientific Publishers
Keywords: Adsorption kinetics; Response time; Sensitivity; VOC